2016
DOI: 10.1007/s00441-015-2355-9
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative repair capacity of knee osteochondral defects using regenerated silk fiber scaffolds and fibrin glue with/without autologous chondrocytes during 36 weeks in rabbit model

Abstract: The reconstruction capability of osteochondral (OCD) defects using silk-based scaffolds has been demonstrated in a few studies. However, improvement in the mechanical properties of natural scaffolds is still challengeable. Here, we investigate the in vivo repair capacity of OCD defects using a novel Bombyx mori silk-based composite scaffold with great mechanical properties and porosity during 36 weeks. After evaluation of the in vivo biocompatibility and degradation rate of these scaffolds, we examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…For in vivo evaluation of silk scaffolds, Deng observed improved cartilage regeneration capability of SF/CS scaffolds seeded with BMSC's rather than scaffolds alone 84 . Similar results were obtained by Kazemnejad, where Scaffolds seeded with chondrocytes gave better results than scaffolds alone 85 . The study conducted by Zeng also confirmed the approach of seeding scaffolds with cells where NP cells with silk scaffolds were evaluated both in vitro and in vivo.…”
Section: In Vivo Studiessupporting
confidence: 85%
“…For in vivo evaluation of silk scaffolds, Deng observed improved cartilage regeneration capability of SF/CS scaffolds seeded with BMSC's rather than scaffolds alone 84 . Similar results were obtained by Kazemnejad, where Scaffolds seeded with chondrocytes gave better results than scaffolds alone 85 . The study conducted by Zeng also confirmed the approach of seeding scaffolds with cells where NP cells with silk scaffolds were evaluated both in vitro and in vivo.…”
Section: In Vivo Studiessupporting
confidence: 85%
“…Building on previous results for the interaction of TGF-β with chitosan, we aim to investigate whether combinations with other TGF-β superfamily members, specifically hBMP-6, increases articular cartilage formation potential as compared to the effect of TGF-β 3 used alone or in combination with IGF-I. TGF-β 3 has been described in various studies to promote cartilage repair and accelerate cartilage differentiation, upregulating the expression of genes typical for the formation of cartilage in hADSCs [33,35]. The same genes, however, are activated in growth plate chondrocytes when endochondral ossification ensues.…”
Section: Introductionmentioning
confidence: 99%
“…They support the relevant ECM deposition and stratification, with improved cellular attachment, proliferation, differentiation to the desired phenotype, and integration into the corresponding bone or cartilage defect sites [28,29]. In cartilage-based tissue regeneration, various natural polymers exist, including synthetic alternatives that have been investigated to help in cartilage reformation such as compositions of fiber proteins (collagen, fibrin) [30,31], porous sponge polysaccharides (agarose, alginate, hyaluronic acid, and chitosan) [32,33,34,35], and synthetic hydrogel polymers (polyethylene glycol and polylactic acid) [36,37]. Although synthetic materials allow better control of mechanical, morphological, and physicochemical properties, they more often cause a substantial inflammatory response in vivo than natural materials [38,39].…”
Section: Introductionmentioning
confidence: 99%